Somatic embryogenesis and plant regeneration in Cedrela fissilis - Vila, Silvia Karina (2009)
Somatic embryos were obtained from immature zygotic embryos of Cedrela fissilis Well. (Meliaceae), after a culture period of 12 months, with regular subcultures every 6 - 8 weeks. Callus was developed on explants in 2 months on Murashige and Skoog (MS) medium containing 2,4 dichlorophenoxyacetic acid (2,4-D) or picloram (PIC). When the calli were transferred to fresh medium, embryogenic tissue appeared on MS + 45 µM 2,4-D, or 22.5 µM 2,4-D + 0.4 µM 6-benzyladenine (BA), or 20.7 µM PIC after 6 months. Sub-culture of embryogenic tissue in MS medium supplemented with 4.5 µM 2,4-D resulted in the differentiation into somatic embryos after further 4 months. Repeated secondary somatic embryogenesis was achieved by regular subculture on this medium. Maturation and conversion of somatic embryos into plantlets was achieved on MS medium without plant growth regulators and the conversion frequency was approximately 12.5 %. The plantlets were successfully acclimatized in pots with soil. Histological studies showed that somatic embryos had no detectable connection with the mother explants and that somatic embryos in advanced stages were bipolar with shoot and root apical meristems, they contained vascular system and showed typical characteristics of a somatic dicotyledonous embryo.